2023
DOI: 10.1002/jrs.6512
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of 3000 ppm Cr2O3 doped UO2 and its precipitates

Abstract: The thermochemical state of UO 2 -based nuclear fuel is a key parameter for which experimental data are difficult to obtain. A new experimental procedure using in situ oxido-reduction indicators was applied to irradiated fuel, and we aim to use it with chromium-doped unirradiated UO 2 . Nevertheless, we had first to characterise the chemical state of the chromium precipitates in our sample before. Here, we present the method we used for statistical characterisation of these precipitates using several methods, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Recent high resolution transmission electron microscopy analysis of Cr-doped UO 2 has further identified the significant enrichment of Cr and structural disorder found in precipitate grain boundary regions 46 . Further recent studies by Devillaire et al 47 found evidence for Cr 3 O 4 in these precipitates via Raman spectroscopy, which would involve Cr +2 . It has also been proposed the possibility of Cr +2 occurring within the UO 2 lattice matrix itself with some redox mechanisms between it and Cr +3 which should be observable at ambient conditions.…”
Section: Discussionmentioning
confidence: 73%
“…Recent high resolution transmission electron microscopy analysis of Cr-doped UO 2 has further identified the significant enrichment of Cr and structural disorder found in precipitate grain boundary regions 46 . Further recent studies by Devillaire et al 47 found evidence for Cr 3 O 4 in these precipitates via Raman spectroscopy, which would involve Cr +2 . It has also been proposed the possibility of Cr +2 occurring within the UO 2 lattice matrix itself with some redox mechanisms between it and Cr +3 which should be observable at ambient conditions.…”
Section: Discussionmentioning
confidence: 73%